HOEKOM VERTAAL? - Picard, J.H. (Scientia Militaria - South African Journal of Military Studies, 2012)
Perhaps artistic translations should preferably be left to the artists. Subject-prose translations are, however, indeed possible, even essential for communication purposes as well as for the conveying of knowledge, information and orders. This article discusses the job of the translator, the characteristics of a good translation and what this requires of a translator. The specific task and purpose of the section Foreign Languages of the SADF and its place in a modern national Defence Force, are finally examined.